2014
DOI: 10.1186/1749-8104-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Mesoderm is required for coordinated cell movements within zebrafish neural plate in vivo

Abstract: BackgroundMorphogenesis of the zebrafish neural tube requires the coordinated movement of many cells in both time and space. A good example of this is the movement of the cells in the zebrafish neural plate as they converge towards the dorsal midline before internalizing to form a neural keel. How these cells are regulated to ensure that they move together as a coherent tissue is unknown. Previous work in other systems has suggested that the underlying mesoderm may play a role in this process but this has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
58
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 54 publications
9
58
3
Order By: Relevance
“…For instance, N-cadherin protein was decreased at the membrane of Nodal signaling-deficient embryos at tailbud and early somite stages, but mRNA levels were normal (Aquilina-Beck et al, 2007). Similarly, ZO1 (TJP1a), which is associated with both adherens and tight junctions, was expressed at normal levels in embryos treated with SB505124 at similar stages to our study (Araya et al, 2014). …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…For instance, N-cadherin protein was decreased at the membrane of Nodal signaling-deficient embryos at tailbud and early somite stages, but mRNA levels were normal (Aquilina-Beck et al, 2007). Similarly, ZO1 (TJP1a), which is associated with both adherens and tight junctions, was expressed at normal levels in embryos treated with SB505124 at similar stages to our study (Araya et al, 2014). …”
Section: Discussionsupporting
confidence: 83%
“…Previous studies indicate the developing neural tube is disorganized in Nodal signaling deficient embryos with an open neural tube (Aquilina-Beck et al, 2007; Araya et al, 2014). The organization of the neural tube is mediated by adherens and tight junctions, which form in a step wise fashion.…”
Section: Discussionmentioning
confidence: 99%
“…In wild‐type embryos, neural plate and mesoderm lie very close to each other throughout neurulation (Fig. A–C) (Araya et al, ). In fn1+lamC1 MO embryos, however, we found that small gaps between neural and mesoderm layers were already present at the onset of neurulation (arrowheads in Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Additionally, we have shown that interactions with adjacent tissues like the underlying mesoderm are necessary for coordinated movements of the neural plate cells (Araya et al, ). In fact, our previous analysis indicates that the movements between the neuroectoderm and the underlying mesoderm are highly coupled during initial stages of zebrafish neurulation (Araya et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation